Examining the mediating role of mindful parenting: a study on the relationship between parental emotion regulation difficulties and problem behaviors of children with ASD - AYDIN, AYDAN (My University, 2022)
Parental emotion regulation plays a vital role in the parent-child relationship. This study examines the mediating role of mindful parenting in the relationship between parental emotion regulation difficulties and problem behaviors of children with autism spectrum disorder (ASD). The study was conducted with 273 parents of children with ASD in Istanbul. The study findings revealed a significant yet negative correlation between mindful parenting and emotion regulation difficulty and problem behaviors. The study model highlighted that emotion regulation difficulties significantly predicted mindful parenting and the child\"s problem behavior, whereas mindful parenting significantly predicted the child\"s problem behavior. Additionally, the study findings indicated that mindful parenting was a partial mediator.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Social Sciences and Humanities; Psychology; Developmental Psychology; PSİKOLOJİ, GELİŞTİRME; Temel Bilimler (SCI); PSYCHOLOGY, DEVELOPMENTAL; PSYCHOLOGY; Natural Sciences (SCI); Developmental and Educational Psychology; General Psychology; Psychology (miscellaneous); Social Sciences & Humanities; Autism spectrum disorder (ASD); Parent of child with autism; Emotion regulation difficulty; Mindful parenting; Problem behavior; AUTISM SPECTRUM DISORDER; HIGH-FUNCTIONING AUTISM; PRESCHOOL-CHILDREN; INTERACTIONAL BEHAVIORS; DECREASES AGGRESSION; TURKISH MOTHERS; SOCIAL-BEHAVIOR; STRESS; FAMILIES; FATHERS; Autism spectrum disorder (ASD); Parent of child with autism; Emotion regulation difculty; Mindful parenting; Problem behavior